LINGUOPRAGMATIC STUDY OF HOTEL TOURISM TERMINOLOGY IN UZBEK AND ENGLISH LANGUAGES (Modern education and development, 2025)
This article presents a detailed linguopragmatic analysis of hotel tourism terminology in the Uzbek and English languages. It investigates how specific terms in the tourism and hospitality sector are influenced by cultural, social, and communicative factors in both languages. The paper examines how language is used as a tool for communication in the global hotel industry, exploring the pragmatics of hospitality-related terms and their contextual application. The research highlights the differences and similarities in how these terms function across Uzbek and English, shedding light on the cultural nuances that shape the meaning and usage of hotel tourism terminology.В данной статье представлен подробный лингвопрагматический анализ терминов гостиничного туризма на узбекском и английском языках. Исследование касается того, как конкретные термины в области туризма и гостиничного сервиса формируются под влиянием культурных, социальных и коммуникативных факторов в обеих языках. Работа исследует, как язык используется в качестве инструмента коммуникации в глобальной гостиничной индустрии, анализируя прагматику терминов, связанных с гостиничным сервисом, и их контекстуальное применение. Исследование выявляет различия и сходства в использовании этих терминов в узбекском и английском языках, подчеркивая влияние культурных нюансов на их значение и употребление.Ushbu maqolada o‘zbek va ingliz tillaridagi mehmonxona turizmi terminlarining lingvopragmatik tahlili taqdim etilgan. Tadqiqotda turizm va mehmonxona sanoati kontekstida aniq terminlarning madaniy, ijtimoiy va kommunikativ omillar ta'sirida qanday shakllanishi o‘rganiladi. Maqola global mehmonxona sanoatidagi aloqa vositasi sifatida tilning qanday ishlatilishini tahlil qiladi, shuningdek, mehmonxona bilan bog‘liq atamalarning pragmatik jihatlari va ularning kontekstual qo‘llanilishini o‘rganadi. Tadqiqot o‘zbek va ingliz tillaridagi terminlarning o‘xshashliklari va farqlari haqida tushunchalar beradi, shuningdek, madaniy farqlar ta'sirini yoritadi.